A 3D Anisotropic Cartesian Grid Generation Method and its Applications in Viscosity Flows. (2015) - Shi, Xiaotian; Fang, Shuai; Lv, Meng; Hu, Ning
Abstract: In this paper, a 3D anisotropic Cartesian grid generation method is produced. With this technique, the fine parts of missiles that have small geometry scale can be described with high quality, which of course will improve the aerodynamics prediction accuracy. Viscous Cartesian grids generating of several stand missile models and simulations with finite volume method demonstrate the success of current method. It is found that the prediction accuracy of aerodynamics coefficients are greatly improved companied with results obtained with traditional Cartesian grid generation method, especially for roller moment and yawing moment.